Love, Marriage, Betrayal and Sufferings in Saraswoti Pratikshya's Nathiya (Journal of Population and Development, 2023)
The paper illustrates the various facets of problems and sufferings of the Badi women based on Saraswoti Pratikshya's novel Nathiya. The novel mainly depicts the issues of socio-cultural and economic issues and complications of Badi women. The paper mainly aims to investigate the love, relation, marriage, betrayal, sufferings and other various difficulties of Badi from Dalit Aesthetic perspective. Badi women, as sex workers, are exploited and tortured by non-Dalits clients in different forms. The clients pretend to have love, relation and affairs to Badi women for not to pay their cost; and when the women are in deep love and propose for marriage they get deception, betrayal, tragedy and sufferings. The clients escape from their settlement and they never come back to them. Therefore, most of children are from single-mothers with unidentified fathers. The novel portrays the various facets of problems of Badi women interlinked to caste, culture, economy and socio-culture. The researcher applies the Dalit Aesthetics perspective as theoretical tool for the discussion on the primary text. Moreover, the researcher employs qualitative approach with exploratory method.